Observing mega cities to grow from space and predicting its growth using machine learning techniques - Chakma, Mitesh; Zannat, Sadia (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.